THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED LEARNING USING MACROMEDIA FLASH 8 IN ACCOUNTING COURSE - Wicaksono, Satriyo (Universitas Negeri Malang, 2016)
The development of science and technology influence and bring out the change in the world of education. Utilization of interactive multimedia using Macromedia Flash 8 can be used as a media of learning innovation. The developments of this research using development model 4D, among other steps are define, design, develop, and disseminate, but on this research and development only till to the develop step. The type of data in this development research is using quantitative and qualitative data. Quantitative data obtained from the results of validation experts and users (students and teachers). While the qualitative data in the form of comments and suggestions from validator expert and users. The data obtained from the results of validation to the validator subject matter experts by 83% with a decent sting category, media expert of 97% with a very decent katerogi, and limited testing is said to be very suitable with a percentage of 76%. From the analysis, it can be concluded that the interactive multimedia instructional is valid and suitable for the students.Keywords: development, interactive multimedia, services cycle company